# How do you solve #\frac { 7} { x + 6} + \frac { 5} { x - 6} = \frac { 6} { ( x + 6) ( x - 6) }#?

##### 2 Answers

#### Explanation:

Let's solve your equation step-by-step.

Multiply all terms to get

Check the answer. (Plug it in to make sure it works)

Answer:

(

#### Explanation:

First, rule out the solutions

Now, multiply both sides by

#7(x-6)+5(x+6)=6 " "x !in{-6,6}#

From here, distribute and solve normally, keeping in mind the extraneous solutions -6 and 6.

#7x-42+5x+30=6 color(white)"XXXXX" x!in{-6,6}#

#color(white)"XXX/XX"12x-12=6 color(white)"XXXXX"x!in{-6,6}#

#color(white)"XXXXXXXX.." 12x=18 color(white)"XXXX."x!in{-6,6}#

#color(white)"XXXXXXXXXX" x=3/2#

*Final Answer*